Influence of economic factors on performance of investment and Mudharabah accounts in Maybank, Malaysia - Zainal, Noor Saliza; Mohd. Yusof, Zulkafli; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
This study examines relationship between investment and Mudharabah accounts in Maybank with economic factors. The data used are secondary data from various annual reports of Maybank from 1996 until 2007. The data are analyzed using Correlation and Multiple Regression analysis. The dependent variables studied are total investment and Mudharabh accounts and set of independent variables comprised of gross domestic product (GDP), unemployment rate (UER), income percapita (IPC) and consumer price index (CPI). The main objectives are to identify the relationship between the independent variables and to examine their influence on total deposits of investment and Mudharabah accounts. The results of Correlation showed that there is no relationship between all independent variables. The findings also proved that UER, GDP, IPC and CPI have significant relationships with investment and Mudharabah accounts. Finally, this study confirmed that UER is the most dominant factor that influenced both investment and Mudharabah accounts.